ADAPTING TO SHIFTS: ANALYZING THE IMPACT OF CLIMATE CHANGE ON LIVELIHOODS IN KAPSOKWONY DIVISION, MT. ELGON - Jennings , Sarah (Ayden Journal of Agriculture and Allied Studies, 2024)
Climate change poses a significant threat to mountain ecosystems worldwide, exacerbated by various anthropogenic stressors such as land encroachment, fragmentation, habitat degradation, and destruction. This complex interaction has farreaching consequences for livelihoods, particularly in regions like Kapsokwony Division, Mt. Elgon Sub-County, where agriculture and ecosystem services play a vital role. As climate change and variability lead to erratic and unpredictable rainfall patterns, agricultural productivity is declining, resulting in reduced soil fertility due to erosion and increased evapo-transpiration. According to the IPCC, temperature increases beyond 1.5°C - 2.5°C can have severe impacts on land productivity and livelihoods. In this context, households in Kapsokwony Division are predominantly reliant on crop farming, livestock rearing, and non-farm activities. The adverse effects of climate change are most pronounced among poor households, which face additional barriers stemming from cultural, social, and political factors, limiting their access to resources, knowledge, and decisionmaking opportunities. This study sheds light on the multifaceted challenges faced by vulnerable communities in the wake of climate change and highlights the urgent need for context-specific mitigation and adaptation strategies.